PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN PADA PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - HALIMAH "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The aim of this research is to analyze the implementation of Customer Relationship Management and customer loyality of PT. Bank Riau Kepri Pekanbaru Main Branch and see its effects. Results of the study concluded that the implementation of CRM in PT. Bank Riau Kepri Pekanbaru Main Branch that includes dimension of direct sales, direct customer relationship, customer segmentation for ssales and service, and build-to-order production. have been rated good overall. Customer loyality of PT. Bank Riau Kepri Pekanbaru Main Branch that is seen from the dimension of re-purchase on a regular basis, refer to other consumers, and the desireremains a customer are also rated high. The results of data analysis through SPSS programs, CRM has a strong connection to the customer's loyalitas. CRM provide variable positive and significant influence on the customer loyality on variable PT. Bank Riau Kepri Pekanbaru Main Branch, which means that if the variable is improved then the CRM will also cause an increase of the customer loyality.Keyword: customer relationship management, customer loyality, Bank Riau Kepri